Serologic Profile of Antiparietal Cell Antibodies, Pepsinogens, and H. pylori and Risk of Upper Gastrointestinal Cancer: A Nested Case–Control Study in China - Wang, Shao-Ming; Roth, Mark J.; Murphy, Gwen A.; Dawsey, Sanford M.; Fan, Jin-Hu; Taylor, Philip R.; Qiao, You-Lin; Abnet, Christian C. (Cancer epidemiology, biomarkers & prevention, 2019)
Autoimmune gastritis is understudied and possibly associated with gastric noncardia adenocarcinoma (GNCA) and esophageal squamous cell carcinoma (ESCC) in Western populations when it presents as pernicious anemia. A nested case-control study within a Chinese cohort included 100 ESCC, 200 gastric cardia adenocarcinoma (GCA), and 200 GNCA cases diagnosed between 1986 and 2001 and 400 controls. Serostatus of antiparietal cell antibodies (APCA), antibodies, and pepsinogens were measured using commercial kits and serum collected at baseline. We used logistic regression to calculate odds ratios (OR) and 95% confidence interval (CI) for associations between serologic biomarkers and cancer risk adjusted for numerous potential confounders. There was an average interval of 8 years between baseline blood draw and cancer diagnosis. The baseline prevalence of APCA seropositivity was 10.0% and 14.5% in subjects who developed GCA and GNCA, respectively. APCA seropositivity was inversely associated with later development of GCA (OR = 0.42; 95% CI, 0.24-0.75), but not significantly associated with later development of GNCA (OR = 0.82; 95% CI, 0.50-1.36) or ESCC (OR = 1.05; 95% CI, 0.58-1.88). APCA seropositivity was significantly associated with low pepsinogen I/II ratios (OR = 3.69; 95% CI, 1.66-8.21), and individuals with low pepsinogen I/II ratios who were seronegative for APCA had the highest risk of both GCA and GNCA. APCA seropositivity measured years prior to diagnosis was associated with prevalent atrophic gastritis but inversely associated with incident GCA in this Chinese population. APCA may contribute to a growing list of serologic markers that can improve risk stratification for gastric cancer.